2015
DOI: 10.1002/2015ja021395
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electron response to the combined magnetospheric impact of a coronal mass ejection overlapping with a high‐speed stream: Van Allen Probes observations

Abstract: During early November 2013, the magnetosphere experienced concurrent driving by a coronal mass ejection (CME) during an ongoing high‐speed stream (HSS) event. The relativistic electron response to these two kinds of drivers, i.e., HSS and CME, is typically different, with the former often leading to a slower buildup of electrons at larger radial distances, while the latter energizing electrons rapidly with flux enhancements occurring closer to the Earth. We present a detailed analysis of the relativistic elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
3
17
0
Order By: Relevance
“…Figures a–d show an example electron spectrum taken following a magnetic storm [ Kanekal et al ., ]. These show a peak in the phase space density radial profiles formed over a range of first invariant values (Figures c and d), similar to those from Reeves et al .…”
Section: Van Allen Probes Energetic Particle Sensorssupporting
confidence: 82%
See 2 more Smart Citations
“…Figures a–d show an example electron spectrum taken following a magnetic storm [ Kanekal et al ., ]. These show a peak in the phase space density radial profiles formed over a range of first invariant values (Figures c and d), similar to those from Reeves et al .…”
Section: Van Allen Probes Energetic Particle Sensorssupporting
confidence: 82%
“…This background correction capability was used to make new measurements of the electron fluxes and spectra in the inner radiation zone [ Fennell et al ., ] and to produce data free from Bremsstrahlung for multiple storm time studies such as those by Kanekal et al . [], Jaynes et al . [], Turner et al .…”
Section: Van Allen Probes Energetic Particle Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although energetic electron injections during substorms or enhanced convection provide seed electrons (from tens of keV to hundreds of keV) [ Miyoshi et al ., ; Baker and Kanekal , ; Thorne , ; Boyd et al ., ; Dai et al ., ; Jaynes et al ., ], this process is unlikely to directly lead to the net electron acceleration up to multiple MeV. Inward radial diffusion caused by interaction with Ultra‐Low‐Frequency (ULF) waves can accelerate electrons to higher energies [ Hudson et al ., ; Mathie and Mann , ; Perry et al ., ; Ukhorskiy et al ., ], but this process alone is unlikely to account for the observed outer radiation belt electron dynamics which often exhibits growing radial peaks in electron phase space density (PSD) at ultrarelativistic energies in the heart of the radiation belts [ Green and Kivelson , ; Iles et al ., ; Chen et al ., ; Turner et al ., ; Reeves et al ., ; Thorne et al ., ; Kanekal et al ., ]. This suggests that an internal heating process is operating, and the potential candidates for this local acceleration include energy diffusion by chorus and magnetosonic (MS) waves [e.g., Summers et al ., ; Horne et al ., , , ; Thorne et al ., ; Ma et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding how electrons are accelerated to ultrarelativistic energies in the radiation belts, several mechanisms have been considered to be potentially important. Although energetic electron injections during substorms or enhanced convection provide seed electrons (from tens of keV to hundreds of keV) [Miyoshi et al, 2003;Baker and Kanekal, 2008;Thorne, 2010;Boyd et al, 2014;Dai et al, 2014;Jaynes et al, higher energies [Hudson et al, 1999;Mathie and Mann, 2000;Perry et al, 2005;Ukhorskiy et al, 2009], but this process alone is unlikely to account for the observed outer radiation belt electron dynamics which often exhibits growing radial peaks in electron phase space density (PSD) at ultrarelativistic energies in the heart of the radiation belts [Green and Kivelson, 2004;Iles et al, 2006;Chen et al, 2007;Turner et al, 2014;Reeves et al, 2013;Thorne et al, 2013a;Kanekal et al, 2015]. This suggests that an internal heating process is operating, and the potential candidates for this local acceleration include energy diffusion by chorus and magnetosonic (MS) waves [e.g., Summers et al, 2002;Horne et al, 2005aHorne et al, , 2005bHorne et al, , 2007Thorne et al, 2013a;Ma et al, 2016].…”
Section: Introductionmentioning
confidence: 99%